Evaluación de la adición de polvo de ladrillo en la mezcla de cemento, para la producción de prefabricados de concreto en la empresa Reciclados Industriales de Colombia (2018)
In the present work of degree, develops an experimental design, which has the hypothesis that the construction and demolition waste as in this case the brick dust with the ceramics, have cementing properties that could resemble those of cement Once this raw material is added to the binder material at certain quantities, which could possibly cause the improvement of the characteristics of a conventional concrete or at least compare them. For this, through the realization of different mechanical tests, which specifically govern the characteristics that a cement must have in order for it to be used in the construction industry; it has the following characteristics more required in the market: The determination of the setting time, NTC 118; the determination of the Resistance of Mortars, NTC 220, the test of Finura de Blaine, NTC 33 and the determination of the Resistance to the Compression of Concrete Cylinders, NTC 673, among others; all evaluated by means of procedures described in the current Colombian Technical Standards (NTC). Similarly, the development of three fundamental chemical tests, such as: X-Ray Fluorescence, Thermogravimetric Analysis (TGA) and Laser Granulometry, seek to investigate more thoroughly the chemical behavior of the compounds that make up the mixture; and in turn, it has the purpose of specifying the appropriate particle size of the addition that achieves a better reaction of it. Among the main results comparing a cement with 0% debris repl acement, against 75% in cement and 25% addition of brick powder, this being the most feasible replacement in terms of gain in resistances.